2017
DOI: 10.1093/cercor/bhx171
|View full text |Cite
|
Sign up to set email alerts
|

A  Complex Code of Extrinsic Influences on Cortical Progenitor Cells of Higher Mammals

Abstract: Development of the cerebral cortex depends critically on the regulation of progenitor cell proliferation and fate. Cortical progenitor cells are remarkably diverse with regard to their morphology as well as laminar and areal position. Extrinsic factors, such as thalamic axons, have been proposed to play key roles in progenitor cell regulation, but the diversity, extent and timing of interactions between extrinsic elements and each class of cortical progenitor cell in higher mammals remain undefined. Here we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 105 publications
1
41
0
Order By: Relevance
“…In addition, gain-offunction experiments, either in transgenic HAR-14q12 mice or targeted humanized mouse ESC-derived 3D forebrain organoids resulted in the expansion of neuroepithelial and radial glia progenitors. Our results provide an additional mechanism that has potentially contributed to the shorter cell cycle and higher proliferative potential of RG progenitors, which is proposed to drive the evolutionary expansion of the mammalian telencephalon (Calegari et al, 2005;Pilz et al, 2013;Betizeau et al, 2013;Pilaz et al, 2009;Reillo et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, gain-offunction experiments, either in transgenic HAR-14q12 mice or targeted humanized mouse ESC-derived 3D forebrain organoids resulted in the expansion of neuroepithelial and radial glia progenitors. Our results provide an additional mechanism that has potentially contributed to the shorter cell cycle and higher proliferative potential of RG progenitors, which is proposed to drive the evolutionary expansion of the mammalian telencephalon (Calegari et al, 2005;Pilz et al, 2013;Betizeau et al, 2013;Pilaz et al, 2009;Reillo et al, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…bRG in hNcx exhibited a greater average number of radial processes than bRG in fNcx and mNcx. In addition to the radial processes, we detected a number of smaller protrusions of bRG, previously termed lamellate expansions (Rakic, 1972;Reillo et al, 2017), in hNcx and fNcx, but not mNcx (Figures 2C 00 ,S2O,and S2P).…”
Section: Quantitative Analysis Of Bp Morphotypes Across Different Mammentioning
confidence: 93%
“…BPs in ferret and primates show diverse morphologies (Betizeau et al, 2013;Reillo et al, 2017), some of which have also been observed in mNcx (Pilz et al, 2013;Wong et al, 2015). bRG were originally described as monopolar cells with a long basal process that often contacts the basal lamina (Fietz et al, 2010;Hansen et al, 2010;Reillo et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…(legend continued on next page) and influence progenitor cell proliferation, neuronal migration, and differentiation in rodents (Le Magueresse and Monyer, 2013;LoTurco et al, 1995;Weissman et al, 2004). Progenitor cells, maturing excitatory neurons and interneurons, endothelial cells, and the cerebrospinal fluid (CSF) are all potential sources of neurotransmitters (Bonnin et al, 2011;Le Magueresse and Monyer, 2013;Lehtinen et al, 2011;Li et al, 2018;Manent et al, 2005;Reillo et al, 2017;Weissman et al, 2004). Additionally, axons from extracortical regions such as the diencephalon and brain stem innervate the cortex and affect cortical development (Bonetti and Surace, 2010;Chen and Kriegstein, 2015;Duque et al, 2016;Reillo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%